2006
DOI: 10.1103/physrevb.73.174517
|View full text |Cite
|
Sign up to set email alerts
|

Two-band model of Raman scattering on electron-doped high-Tcsuperconductors

Abstract: We have analyzed the B1g and B2g Raman spectra of electron-doped cuprate superconductors Nd2−xCexCuO4 and Pr2−xCexCuO4 using a weakly coupled two-band model. One of these two bands is centered around (±π/2, ±π/2) and couples more strongly with the B2g mode, while the other is centered around (±π, 0) and (0, ±π) and couples more strongly with the B1g mode. This model explains in a natural way why the B2g Raman peak occurs at a higher frequency than the B1g one at optimal doping, and how these two peaks change w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 30 publications
1
11
0
Order By: Relevance
“…The entire LDOS is obtained as i i i r r r = +   . Before we present our numerical results, it is necessary to clarify that our present model is actually an effective two-band model in the presence of AF order, qualitatively consistent with the two-band model proposed by [5,6]. Without the impurity term and considering a uniform AF order, we can transform the Hamiltonian to momentum space.…”
Section: Model and Hamiltoniansupporting
confidence: 66%
See 2 more Smart Citations
“…The entire LDOS is obtained as i i i r r r = +   . Before we present our numerical results, it is necessary to clarify that our present model is actually an effective two-band model in the presence of AF order, qualitatively consistent with the two-band model proposed by [5,6]. Without the impurity term and considering a uniform AF order, we can transform the Hamiltonian to momentum space.…”
Section: Model and Hamiltoniansupporting
confidence: 66%
“…Based on angle-resolved photoemission experiments, it was revealed that there are two disconnected Fermi surface pockets [2,3], and thus, an effective two-band model may be required to describe electron-doped SC materials. Theoretically, several two-band models have indeed been proposed to account for low-energy properties [4][5][6][7]. Possible microscopic origins have been intensively discussed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that the reduced resistive upper critical field for NCCO is largely independent of disorder type and amount, it is unlikely that the observed temperature dependence is dominated by disorder effects, but rather signifies a universal underlying characteristic of the doped CuO 2 planes of the electron-doped cuprates. Raman scattering experiments ( 45 , 46 ) also reveal that the coherent normal-state hole quasiparticles contribute to the superfluid density. Moreover, the superfluid response obtained from penetration depth measurements points to dual electron and hole contributions ( 39 , 47 ).…”
Section: Discussionmentioning
confidence: 99%
“…The model requires different pairing strengths of electrons and holes in electron-doped cuprates, which is also used to ascribe the feature in Raman scattering on Nd 2−x Ce x CuO 4 and Pr 2−x Ce x CuO 4 [151].…”
Section: Manifestation Of Two Bands In Mixed Statementioning
confidence: 99%